Penerapan Customer Relationship Management (CRM) di Alfamart - Sabina Siti Sholeha; Theresia Longga; Muhammad Hilmana Chaska (Universitas 45 Surabaya, 2025)
Customer Relationship Management (CRM) is a strategic approach that companies use to manage interactions and relationships with customers. In Indonesia, Alfamart as one of the largest minimarket chains implements CRM to increase customer satisfaction, loyalty, and ultimately, increase sales. This study aims to analyze the implementation of CRM in Alfamart, as well as its impact on customer satisfaction and loyalty.